A Romance perspective on language knowledge and use - Núñez, Rafael (Núñez Cedeño); López, Luis, 1965-; Cameron, Richard, 1953- (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2003)
Twenty-one articles from the 31st LSRL investigate cutting-edge issues and interfaces across phonology, pragmatics, sociolinguistics, semantics, and syntax in multiple dialects of such Romance languages as Catalan, French, Creole French, and Spanish, both old and modern. Research in Romance phonology moves from the quantitative and synchronic to cover issues of diachrony and Optimality theory. Work within pragmatics and sociolinguistics also explores the synchronic/diachronic link while topicalizing such issues as change of non-pro-drop Swiss French toward pro-drop status, scalar implicatures.